Development and validation of children's mind wandering scales - Cao, Zhiwei; Huang, Ying; Song, Xiaolan; Ye, Qun (Frontiers in Public Health, 2022)
Introduction Mind wandering is generally considered an endogenous mental state that arises spontaneously, which is one of the most common experiences of consciousness and typically occurs at a significant cost to mental health and behavioral performance. Previous studies have shown that mind wandering appears to be a stable trait and can be assessed reliably in adults. Surprisingly little, however, is known about how to measure the frequency of mind wandering in children, given that children can accurately introspect their experiences. The present studies aimed to develop the Frequency of Children's Mind Wandering Scale (CMWS-F) and the Context of Children's Mind Wandering Scale (CMWS-C) to assess the frequency of mind wandering and contexts in which mind wandering occurs for children aged 8 to 11 years. Methods The exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) were used to develop the CMWS-F and CMWS-C. To further assess the validity of the scales, we compared the scores in CMWS-F/CMWS-C and the frequencies of probe-caught mind wandering in the typical tasks. Results In study 1a, the EFA (n = 292) and CFA (n = 346) showed that attentional failure and spontaneous thinking were the two main dimensions of CMWS-F. In study 1b, contexts about mind wandering in children could be divided into high-demand and low-demand contexts using EFA (n = 258) and CFA (n = 347). Study 2 showed moderate positive correlations between the frequencies of probe-caught mind wandering in the tasks and the scores in the scales. Discussion The results showed that scores on the two scales could predict the performance on the experimental tasks and further demonstrated empirical validity of the CMWS-F and CMWS-C scales. Taken together, the results of the current studies provided preliminary evidence for the validity and reliability of CMWS-F and CMWS-C in children, which can be used as a reference to balance its downsides and productive aspects of mind wandering.